Body fat stigma in gyms: consequences for adherence to nutritional monitoring (Research, Society and Development, 2022)
The increase of obesity in the world and the stigma suffered by individuals with excess body fat in various environments is notorious. Fitness centers end up reinforcing it and may influence psychosocial aspects and adherence to nutritional monitoring. This study aimed to relate the consequences of the stigma of body fat in gyms with the adherence to nutritional monitoring. This was a cross-sectional and descriptive study. The sample was composed of 56 individuals (18 to 59 years old), of both genders, with BMI between 18.5 and 40 kg/m², who attend or have attended gyms. A questionnaire was applied, divided into three themes: sociodemographic data, stigma in the gym, and nutrition in gyms. The data were tabulated in MS Excel and statistically analyzed using SPSS software (version 21), comparing the variables using the chi-square and having a statistical relationship of p